Diagnostic efficacy of contrast-enhanced fluid-attenuated inversion recovery (FLAIR) imaging in idiopathic cerebrospinal fluid rhinorrhea - Hiroaki Watanabe; Hidetoshi Arai; Kazuho Ogihara; Hiroyuki Morisaka; Akitoshi Saito; Motohiro Moriyama; Shin Nakano; Kenta Aonuma; Kaori Aoyagi; Keiko Matsumoto; Keiji Toyama; Hiroshi Onishi (Radiology Case Reports, 2024)
We report a case of a 50-year-old woman in which contrast-enhanced fluid-attenuated inversion recovery (FLAIR) was used for the diagnosis of idiopathic cerebrospinal fluid rhinorrhea. The pre- and postcontrast FLAIR subtraction images showed a contrasted protrusion of the right olfactory cleft canal, highlighting the potential practicality and effectiveness of using pre- and postcontrast FLAIR subtraction images in diagnosing idiopathic cerebrospinal fluid rhinorrhea, in conjunction with conventional high-resolution computed tomography and magnetic resonance cisternography. The successful diagnosis of cerebrospinal fluid rhinorrhea allowed for treatment through endoscopic nasal surgery to close the fistula with a positive clinical outcome.